4x+3=9x+4-1

Simple and best practice solution for 4x+3=9x+4-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+3=9x+4-1 equation:


Simplifying
4x + 3 = 9x + 4 + -1

Reorder the terms:
3 + 4x = 9x + 4 + -1

Reorder the terms:
3 + 4x = 4 + -1 + 9x

Combine like terms: 4 + -1 = 3
3 + 4x = 3 + 9x

Add '-3' to each side of the equation.
3 + -3 + 4x = 3 + -3 + 9x

Combine like terms: 3 + -3 = 0
0 + 4x = 3 + -3 + 9x
4x = 3 + -3 + 9x

Combine like terms: 3 + -3 = 0
4x = 0 + 9x
4x = 9x

Solving
4x = 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
4x + -9x = 9x + -9x

Combine like terms: 4x + -9x = -5x
-5x = 9x + -9x

Combine like terms: 9x + -9x = 0
-5x = 0

Divide each side by '-5'.
x = 0

Simplifying
x = 0

See similar equations:

| [(12x)(14i)]-[sin(xy)/2.362x] | | x-(-3.3)/-3=-2.9 | | -1.5x-2=-.5x-2 | | (y^5x^2)/(y^4x^6) | | z-(-3.3)/3=2.9 | | z-3.3/-3=-2.9 | | 3x-8t=-8 | | 5/6*-6/7 | | 2x+7+10=11x | | 1.7(r+1)=6.8 | | 9-4(2x-1)=45-4x | | (-3-7)+(4+7)= | | -152=4(-8+5m) | | b/9=a | | b/9=8 | | 38n+1=25 | | 3=-4/w-7 | | 3(-5a+9)-2(4a+6)= | | 5.25(2)+3.25=10.25+1.75(2) | | 6x^3-12x^2+10x-20=0 | | -10w+2=2w+18 | | 13x+11=12x+3 | | 2(4x+7)+6x=5(x+10) | | -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 |

Equations solver categories